On the Neotropical genus Adcatomus Karsch (Araneae: Sparassidae) - Rheims, Cristina Anne (Zootaxa, 2008)
The genus Adcatomus Karsch, 1880 is revised. The male of the type species, A. ciudadus Karsch, 1880 is redescribed based on recently collected material from Venezuela, and the female is described for the first time based on material from the same locality. In addition, the monotypic genus Spatala Simon, 1897 is considered a junior synonym of Adcatomus and thus, S. flavovittata Simon, 1897 also described from Venezuela is transferred to that genus.